Perbandingan Efektivitas Metode Pembelajaran Luring dan Daring Terhadap Pemahaman Siswa - Husnul Hotimah; Fadilatunnisa Fadilatunnisa; Mei Wulida; Wahyu Hidayat; Dina Indriana (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to analyze the differences in effectiveness between online and offline learning methods in terms of material understanding, lecturer-student interaction, independent learning time management, and student learning motivation. The method used is quantitative with data collection through questionnaires and literature studies to explore the topic being studied. The results of the study indicate that offline learning is more effective in improving material understanding, lecturer-student interaction, and learning motivation. As many as 78% of students have difficulty understanding the material during online learning, and interaction with lecturers is more limited. However, there is no significant difference in independent learning time management between the two methods. The Mann Whitney test shows a p-value of 0.000, which indicates a significant difference between the effectiveness of online and offline learning.